Effect of Company Income Tax on Corporate Performance of Listed Manufacturing Firms in Nigeria - Ojelabi, Sunday Adeyemi (Advances in Social Sciences Research Journal, 2023)
The conundrum of the Nigerian economy is traceable to its manufacturing sector which is expected to stimulate the value-added economy and serve as a catalyst for sustainable economic transformation. Regrettably, Nigeria’s Manufacturing sector has been neglected without a clear policy direction with attendant annihilation of the sector from the growth process. This becomes evident following the low share of manufacturing sector contribution to GDP and plummeted employment generation capacity of the sector (Ogudu, et at., 2018). Nigeria’s ostentatious importation of manufactured products and weak export base of finished goods remains an undeniable signal to the inchoate weakness of the manufacturing sector. Meanwhile, the weak performance of the manufacturing sector is also evidenced in the low share of non-oil exports to total exports earnings, coupled with high share of manufactured goods in total imports (Ogudu, et at., 2018).